(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
The main objective of this study was to evaluate an educational strategy called Aula País. The sample consisted of 1000 students from the Fundación Universitaria del Área Andina, Colombia; there was also a sample of 200 students from different faculties and programs. The instrument of perceptions and evaluation of the impact of the country classroom strategy was used. The results indicate an active participation by the student body, the generation of various proposals, but it should be noted that this project is still in the process of development. In conclusion, aula país consolidates a pedagogical strategy for the social transformation of the country, from the voice of young people with a simple methodological structure that includes: expository videos, lectures, debates, guides for the writing of proposals and theoretical and audiovisual repositories.